Colitis Linked to Endoplasmic Reticulum Stress Induces Trypsin Activity Affecting Epithelial Functions. (20th February 2021) - Solà Tapias, Núria; Denadai-Souza, Alexandre; Rolland-Fourcade, Claire; Quaranta-Nicaise, Muriel; Blanpied, Catherine; Marcellin, Marlène; Edir, Anissa; Rolland, Corinne; Cirillo, Carla; Dietrich, Gilles; Alric, Laurent; Portier, Guillaume; et al.
Abstract: Background and Aims: Intestinal epithelial cells [IECs] from inflammatory bowel disease [IBD] patients exhibit an excessive induction of endoplasmic reticulum stress [ER stress] linked to altered intestinal barrier function and inflammation. Colonic tissues and the luminal content of IBD patients are also characterized by increased serine protease activity. The possible link between ER stress and serine protease activity in colitis-associated epithelial dysfunctions is unknown. We aimed to study the association between ER stress and serine protease activity in enterocytes and its impact on intestinal functions Methods: The impact of ER stress induced by Thapsigargin on serine protease secretion was studied using either human intestinal cell lines or organoids. Moreover, treating human intestinal cells with protease-activated receptor antagonists allowed us to investigate ER stress-resulting molecular mechanisms that induce proteolytic activity and alter intestinal epithelial cell biology. Results: Colonic biopsies from IBD patients exhibited increased epithelial trypsin-like activity associated with elevated ER stress. Induction of ER stress in human intestinal epithelial cells displayed enhanced apical trypsin-like activity. ER stress-induced increased trypsin activity destabilized intestinal barrier function by increasing permeability and by controlling inflammatory mediators such as C-X-C chemokine ligand 8 [CXCL8]. The deleterious impact of ER stress-associated trypsin activity was specifically dependent on the activation of protease-activated receptors 2 and 4. Conclusions: Excessive ER stress in IECs caused an increased release of trypsin activity that, in turn, altered intestinal barrier function, promoting the development of inflammatory process.